3D object recognition using MANFIS network with orthogonal and non-orthogonal moments - M. Khusairi, Osman; Mohd Yusoff, Mashor; M. Rizal, Arshad; Zuraidi, Saad (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org